Knowledge, Practice and Associated Factors Towards Medication Abortion Among Reproductive-Age Women in Sexual and Reproductive Health Clinics of Addis Ababa, Ethiopia, 2018: Cross-Sectional Study - Yeshambel Wassie A; Berhe Lemlem S; Boka A (Dove Medical Press, 2021)
Addisu Yeshambel Wassie,1 Semarya Berhe Lemlem,2 Abdisa Boka2 1Department of Midwifery, College of Health Science and Medicine, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 2School of Nursing and Midwifery, College of Health Science, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Addisu Yeshambel WassieDepartment of Midwifery, College of Health Science and Medicine, Wolaita Sodo University, Wolaita Sodo, EthiopiaTel +251926725128Email addisyes3@gmail.comBackground: Abortion rates following unintended pregnancies are increasing in developing countries, and unsafe abortion is a commonly neglected reproductive health-care problem. In Ethiopia, the number of women receiving treatment for complications from unsafe abortion is increasing. Improving the level of knowledge of reproductive-age women on medication abortion contributes to the prevention of unsafe abortion. Therefore, the purpose of this study was to assess knowledge, and practice of medication abortion and associated factors among women in SRH clinics of Addis Ababa, Ethiopia, 2018.Methods: A cross-sectional quantitative study design was conducted to collect data from 30th February to March 30, 2018. Study participants were selected by using a convenient sampling technique. The data were coded and entered into EpiData version 4.2, and SPSS version 23 was used for analysis. Bivariate and multivariate analysis with 95% CI were employed. The strength of association was declared at a P value < 0.05.Results: The overall knowledge and practice of medication abortion were 72.1%, and 33%, respectively. Participants level of education (AOR=3.54, 95% CI (1.02, 12.26)), father education (AOR=2.80, 95% CI (1.42, 5.52)), participants way of living (AOR=6.08, 95% CI (2.41, 15.33)), income (AOR=2.19, 95% CI (1.02, 4.75)), and history of unwanted pregnancy (AOR=11.7, 95% CI (1.11, 12.46)) were some of the factors associated with knowledge and practice of medication abortion.Conclusion: This study provided that women were relatively knowledgeable but their practice on medication abortion was low. The low practice of medication abortion call health-care providers to give due attention to awareness creation and strengthened action to provide quality maternal care for childbearing mothers towards medication abortion and unsafe abortion in particular.Keywords: knowledge, practice, medication abortion, reproductive-age women